Proteomics of the epicardial fat secretome and its role in post-operative atrial fibrillation. Issue 7 (5th June 2017) - Viviano, Alessandro; Yin, Xiaoke; Zampetaki, Anna; Fava, Marika; Gallagher, Mark; Mayr, Manuel; Jahangiri, Marjan
Abstract: Aims: Post-operative atrial fibrillation (POAF) is a predictor of morbidity and mortality after cardiac surgery. Latent predisposing factors may reside in the epicardial adipose tissue (EAT) due to its anatomical position and high protein production rate. In order to explore a possible mechanistic link, we characterized proteins secreted by the EAT preceding the onset of POAF. Methods and results: Epicardial adipose tissue samples were collected from 76 consecutive patients with no history of AF undergoing coronary artery bypass surgery, 50 samples for proteomic analysis and 26 for gene expression studies, further divided according to development of POAF. Ten vs. 10 matched samples representing EAT secretome were analysed by two-dimensional difference in-gel electrophoresis (2D-DIGE) and high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) to identify differentially expressed proteins ( P  < 0.05, expression change >1.2 fold). Findings were validated by Western blotting on EAT protein extracts and by gene expression studies via quantitative polymerase chain reaction (qPCR). Proteomics returned 35 differentially expressed proteins. Amongst those, gelsolin was down regulated in POAF. Western blot analysis confirmed a significant reduction in gelsolin in the AF group. Gene expression for gelsolin was significantly reduced in the AF group confirming the proteomics findings. Conclusion: For the first time we describe EAT secretome as a possible substrate for POAF. It contains various proteins differentially expressed in patients who later develop POAF. Amongst those gelsolin, involved in inflammation and ion channel regulation, was associated with maintenance of sinus rhythm. Understanding the role of EAT may offer novel insights into prevention and treatment of AF.